Pengaruh Capital Intensity dan Inventory Intensity terhadap Tax Avoidance (Studi Empiris pada Perusahaan Sektor Industri yang terdaftar di BEI Periode 2018-2022) - Rezi Putri Wardani; Nidia Anggreni Das; Juita Sukraini (Politeknik Raflesia Press, 2025)
This type of research is quantitative and associative research with cause and effect relationships at the level of explanation. The unit of analysis for this research is manufacturing companies listed on the Stock Exchange from 2018 to 2022. The population of this research aws 59 companies, the sample size was 12 companies, and the sample size was 60 companies. The result of this study show that capital intensity has no effect on tax avoidance, inventory intensity have no effect tax avoidance. The finding of this research provide understanding to business managers that investors and potential inventors have a valid reference in making investment decisions, especially with increasing capital and inventory intensity, especially in corporate tax avoidance.